The inverse eigenvalue problem for a Hermitian reflexive matrix and the optimization problem - Gigola, Silvia; Lebtabi, Leila; Thome, Néstor (Journal of Computational and Applied Mathematics, 2017)
The inverse eigenvalue problem and the associated optimal approximation problem for Hermitian reflexive matrices with respect to a normal {k+1}-potent matrix are considered. First, we study the existence of the solutions of the associated inverse eigenvalue problem and present an explicit form for them. Then, when such a solution exists, an expression for the solution to the corresponding optimal approximation problem is obtained. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: eigenvalues; generalized inverses; hermitian matrix; optimization problem; JCR; Scopus